Physiology of Cholangiocytes. Issue 1 (January 2013) - Tabibian, James H.; Masyuk, Anatoliy I.; Masyuk, Tetyana V.; O'Hara, Steven P.; LaRusso, Nicholas F.
Abstract: Cholangiocytes are epithelial cells that line the intra‐ and extrahepatic ducts of the biliary tree. The main physiologic function of cholangiocytes is modification of hepatocyte‐derived bile, an intricate process regulated by hormones, peptides, nucleotides, neurotransmitters, and other molecules through intracellular signaling pathways and cascades. The mechanisms and regulation of bile modification are reviewed herein. © 2013 American Physiological Society. Compr Physiol 3:541‐565, 2013.